Predicting of Protein Requirement and Metabolizable Energy on Breast Percentage and Wing Percentages of Local Chickens: A Meta-Analysis - VM Ani Nurgiartiningsih; Osfar Sjofjan; Danung Nur Adli; Anisa Ramadhani (Jurnal Ilmu-Ilmu Peternakan, 2023)
This study aimed to assess the impact of dietary energy and protein balance on carcass weight and percentage during the initial growth phase of local chickens, utilizing a meta-analysis approach. The analysis involved integrating data from 11 articles comprising a total of 120 data points. These articles provided insights into the influence of energy and protein-balanced diets on breast and wing percentages in local chickens. The meta-analysis process involved data collection from diverse scientific publications, standardizing units, and tabulating the information in a Microsoft Excel database. Subsequently, SAS was employed to analyse the tabulated data. The findings revealed that a minimum breast percentage of 30.11% required 18.18% protein, and the associated metabolizable energy requirement was 2974.17 kcal/kg. In summary, achieving a minimum wing percentage of 14.19% necessitated 17.81% dietary proteins and 2943 kcal/kg metabolizable energy for a 14.08% wing percentage.